The Replication Crisis in Psychology: Five Reasons why the Replication Crisis is not Only About Methods - Nielsen, Klaus (International Review of Theoretical Psychologies, 2026)
The replication crisis in psychology is often framed as a methodological failure—an issue of flawed statistical practices, publication bias, and poor experimental design. While these factors undoubtedly play a role, this article argues that the replication crisis is much more than a methodological problem. Psychology’s struggle with replication is not merely a consequence of weak methodologies but a reflection of deeper epistemological, theoretical, historical, political, and institutional challenges within the discipline. In this article, I present five reasons why the replication crisis should be understood as more than just a crisis of methods.